(untitled) (Tanzania Medical Journal, 2021)
Background Knowledge on the assessment of patients' conscious level by using the Glasgow Coma Scale (GCS) among nurses working in the Intensive Care Unit (ICU) and Emergency Medicine Department (EMD) remains a major challenge. Lack of knowledge and expert skills on assessment of conscious level among nurses has been associated with outcomes such as mortality, prolonged hospitalization, and development of complications associated with the primary conditions and hospitalization. This study aimed at assessing the knowledge on GCS scoring among nurses working in EMD and ICU for possible interventions to improve the quality of nursing care to patients in need of close monitoring. Methods The study used a cross-sectional descriptive approach. Data were obtained from 76 nurses working in EMD and ICU recruited by simple random sampling technique. Data were collected by using a self-administered English structured questionnaire after obtaining informed consent from the study participants. Data were then cleaned for missing information analyzed using SPSS computer software version 21. Descriptive and inferential statistics were used to analyze the demographic and knowledge responses. Fisher's exact test was used to determine the association between socio-demographic characteristics and knowledge level; p<0.05 was considered statistically significant. Results This study included 76 nurses; the majority 42(55.3%) working at the ICU. In general, none of the nurses had attended any formal training on GCS Scoring. Majority of the nurses had moderate level of knowledge 51(67.1%) and none had poor knowledge. Although there was no statistically significant difference in knowledge level among the study nurses based on the socio-demographic characteristics, nurses with age 21-30years, working experience 1-3years, and working in ICU, had good knowledge compared to other subgroups. Conclusion and Recommendations The study found that the majority of the nurses had moderate level of knowledge. Since none of them had attended any formal training hence the level of knowledge demonstrated might be from experience sharing and bedside training. The findings suggest the need for post-basic education training for nurses on GCS scoring. In addition, continual profession training focusing at improving nurses’ skills on GCS scoring should be strengthened.